Engaging K–12 Language Learners in Media Literacy. Issue 1 (March 2015) - Egbert, Joy; Neville, Chon
<x xml:space="preserve">Abstract</x> Calls to integrate media literacy into K–12 language classrooms appear to have gone largely unheeded. However, media literacy skills are seen as crucial for 21st‐century learners. This article answers the calls for a focus on media literacy in the language classroom by addressing both why and how systematic attention might be brought to this issue and by highlighting the connections between language and media literacy.